Role of Ombudsman in human rights protection in a contemporary state - Polovchenko, Konstantin A. (Opción, 2019)
The paper presents an analysis of the legal status of the Protector of Citizens (Ombudsman) in the Republic of Serbia. The system analysis method was used allowing a comprehensive review of the ombudsman’s role in protecting the fundamental human rights and freedoms in Serbia. As a result, being an essential element of human rights protection, the Serbian ombudsman was ranked strong; this is also evidenced by the practice of the Protector’s activities. The author comes to the conclusion that the Serbian legislators used the most advanced international experiences in developing the institution of the Protector of Citizens.